Im Kwon-Taek - Chŏng, Sŏng-il 1959-; Yŏnghwa Chinhŭng Wiwŏnhoe (Korea) (Seoul, Korea : Korean Film Council : Seoul Selection, 2006)
"The history of modern Korea consists of many fetters, in which different generations live with very different experiences. Many artists left records rof their generations but Im Kwon-Taek is the only one who has truly embraced all the events of the 20th century and is conveying a message to us now. Just looking at the results, he is nearly the most miraculous survivor but when the personal story of his survival comes to light, the miracle is a record of the tears of a tragic history. Describing Im Kwon-Taek is recording the history of Korean movies and furthermore, explaining the history of modern Korea."--Back cover.
His thoughts I -- His thought II -- Interviews -- Biography -- Filmography -- Endnotes -- References -- About the author.
"Korean Film Council"--Cover.
Filmography: p. 153-177.
Includes bibliographical references and index.
General
Keywords: Im, Kwŏn-t'aek -- Criticism and interpretation; Im, Kwŏn-t'aek -- Critique et interprétation; Im, Kwŏn-t'aek -- Entretiens; Motion picture producers and directors -- Korea -- Biography; Motion picture industry -- Korea -- History -- 20th century; Producteurs et réalisateurs de cinéma -- Corée du Sud -- Biographies; Cinéma -- Corée du Sud -- Histoire